Cronica Facultății în anul universitar 2019-2020 - Trif, Cosmin; Kerekes, Nicolae Dragoș; But-Căpușan, Dacian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
A. PERSONALUL DIDACTIC Pr. prof. univ. dr. Vasile Stanciu Pr. prof. univ. dr. Stelian Tofană Pr. prof. univ. dr. Ioan Chirilă Pr. prof. univ. dr. Ştefan Iloaie Arhim. prof. univ. dr. Cristian (Teofil) Tia Prof. univ. dr. habil. Marcel- Gheorghe Muntean ÎPS prof. univ.dr. Ioan (Andrei) Andreicuţ - pensionar Pr. prof. univ. dr. Alexandru Moraru - pensionar Pr. prof. univ. dr. Valer Bel - pen- sionar Pr. prof. univ. dr. Ioan-Vasile Leb - pensionar